Advancing renewable fuel integration : A comprehensive response surface methodology approach for internal combustion engine performance and emissions optimization - Siaw Paw, Johnny Koh; Kiong, Tiong Sieh; Mohd Kamal, Kamarulzaman; Abdul Adam, Abdullah; Sakinah, Muhamad Hisham; Kadirgama, Kumaran; Devarajan, Ramasamy; Yaw, Chong Tak; Ahmad Fitri, Yusop; Yusaf, Talal F.; A Dhahad, Hayder Abed; Benedict, Foo (Elsevier Ltd, 2023)
In the realm of internal combustion engines, there is a growing utilization of alternative renewable fuels as substitutes for traditional diesel and gasoline. This surge in demand is driven by the imperative to diminish fuel consumption and adhere to stringent regulations concerning engine emissions. Sole reliance on experimental analysis is inadequate to effectively address combustion, performance, and emission issues in engines. Consequently, the integration of engine modelling, grounded in machine learning methodologies and statistical data through the response surface method (RSM), has become increasingly significant for enhanced analytical outcomes. This study aims to explore the contemporary applications of RSM in assessing the feasibility of a wide range of renewable alternative fuels for internal combustion engines. Initially, the study outlines the fundamental principles and procedural steps of RSM, offering readers an introduction to this multifaceted statistical technique. Subsequently, the study delves into a comprehensive examination of the recent applications of alternative renewable fuels, focusing on their impact on combustion, performance, and emissions in the domain of internal combustion engines. Furthermore, the study sheds light on the advantages and limitations of employing RSM, and discusses the potential of combining RSM with other modelling techniques to optimise results. The overarching objective is to provide a thorough insight into the role and efficacy of RSM in the evaluation of renewable alternative fuels, thereby contributing to the ongoing discourse in the field of internal combustion engines.